A Novel and Robust Prognostic Model for Hepatocellular Carcinoma Based on Enhancer RNAs-Regulated Genes - Zhang, Wei; Chen, Kegong; Tian, Wei; Zhang, Qi; Sun, Lin; Wang, Yupeng; Liu, Meina; Zhang, Qiuju (Frontiers in Oncology, 2022)
Evidence demonstrated that enhancer RNAs (eRNAs) play a vital role in the progression and prognosis of cancers, but few studies have focused on the prognostic ability of eRNA-regulated genes (eRGs) for hepatocellular carcinoma (HCC). Using gene expression profiles of HCC patients from the TCGA-LIHC and eRNA expression profile from the enhancer RNA in cancers (eRic) data portal, we developed a novel and robust prognostic signature composed of ten eRGs based on Lasso-penalized Cox regression analysis. According to the signature, HCC patients were stratified into high and low risk groups, which has been shown to have significant differences in tumor immune microenvironment, immune checkpoints, HLA-related genes, DNA damage repair related genes, Gene-set variation analysis (GSVA), and the lower half-maximal inhibitory concentration (IC50) of Sorafenib. The prognostic nomogram combining the signature, age and TNM stage had good predictive ability in training set (TCGA-LIHC) with the concordance index (C-index) of 0.73 and the AUCs for 1-, 3-, and 5-year OS of 0.82, 0.77, 0.74, respectively. In external validation set (GSE14520), the nomogram also performed well with the C-index of 0.71 and the AUCs for 1-, 3-, and 5-year OS of 0.74, 0.77, 0.74, respectively. In addition, an important eRG (AKR1C3) was validated using two HCC cell lines (Huh7 and MHCC-LM3) in vitro, and the results demonstrated that the overexpression of AKR1C3 is related to cell proliferation, migration, and invasion in HCC. Altogether, our eRGs signature and nomogram can predict prognosis accurately and conveniently, facilitate individualized treatment and improve prognosis for HCC patients.